An Experimental Study on Tracking Identity of Moving Shapes: Do Stimulus Complexity and Familiarity Affect Tracking Accuracy of Male and Female Students? - Shuyang Zhang; Hashvini B. Kaliselvan; Tong Zhang; Aini Marina Ma'rof (Faculty of Teacher Training and Education, Universitas Muhammadiyah Surakarta, 2021)
The current study explored the effects of stimulus complexity and familiarity on tracking accuracy between male and female postgraduate students in Malaysia. Since online courses are not restricted by location, the convenience of recording classes has become a steady trend, especially during the COVID-19 period. However, some are also skeptical about the efficacy of online teaching and learning through the digital environment and believe that the stimulus generated on these foundations will result in undesirable consequences (Dhawan, 2020). As student attention determines their tracking accuracy, external factors like stimulus complexity and familiarity tend to be an obstacle for students to be attentive. In this quantitative experimental study named